Environmental carcinogens often exacerbate endogenous mutagenic processes to enhance tumor promotion - Miaofei Xu; Jianying Li; Yun-Chung Hsiao; Ramesh C. Kovi; Jian-Liang Li; Leszek J. Klimczak; Laura Riva; David Adams; Pierre R. Bushel; B. Alex Merrick; Dmitry Gordenin; John R. Bucher; et al. (Cell Reports)
Summary: Environmental exposures significantly influence cancer risk, but their mutational impact remains unclear. We perform whole-exome sequencing of hepatocellular carcinomas (HCCs) from B6C3F1/N mice that arise spontaneously with age (2 years old) or following chronic exposure to one of ten potential human carcinogens that operate through genotoxic or non-genotoxic mechanisms. HCCs from mice exposed to drinking water disinfection byproducts, such as bromochloroacetic acid (BCA) and bromodichloroacetic acid (BDCA), show dose-dependent increases in mutational burden, distinct mutational signatures (BCA-mSBS12 and BDCA-mSBS25), and enrichment of the aTn→aCn mutational motif. In contrast, HCCs from other exposures, as well as from spontaneous tumors, show comparable mutational burdens, mutational signatures, and enrichment of the nCg→nTg mutational motif. These findings suggest that many environmental carcinogens promote tumorigenesis by amplifying endogenous mutagenic processes rather than initiating distinct mutational events. Our results highlight the utility of rodent models for investigating environmental carcinogenesis and provide insights relevant to human cancer risk assessment.